Factors affecting disclosure of HIV-positive serostatus among people living with HIV/AIDS attending an antiretroviral therapy center of Eastern India - Rakesh Kumar; Madhutandra Sarkar; Alok Kumar; Jaya Chakravarty; Sangeeta Kansal (Wolters Kluwer Medknow Publications, 2020)
Background: HIV serostatus disclosure plays an important role in reducing the risk of HIV transmission. However, its negative effects may include rejection, assault, separation, divorce, stigma, and discrimination. Objectives: This study was undertaken to find out the proportion of HIV-positive serostatus disclosure to any family member and different factors influencing disclosure among people living with HIV/AIDS (PLWHA). Methods: A cross-sectional study was conducted among all patients aged 18-49 years with confirmed HIV infection registered at the antiretroviral therapy center of a tertiary care hospital in eastern part of Uttar Pradesh, India, for the duration of 1 year, from July 2017 to June 2018. Results: Most of the respondents were aged 30-49 years (79.9%), male (63.2%), married (85.4%), rural residents (60.4%), Hindu (96.5%), literate (84%), employed/driver (61.8%), and belonged to lower/lower middle class (62.6%). The rate of disclosure of HIV-positive status to any family member was quite high in this study (238/288 or 82.6%), among which 92.9% (221/238) to the spouse only. The number of sexual partners before disclosure, educational status, and socioeconomic status of the respondents were found to be independent predictors of disclosure of HIV-positive status to any family member (P < 0.05). Conclusions: This study indicates the need of giving more emphasis on creating awareness regarding the importance of HIV serostatus disclosure to any family member, especially to spouse, and encourage all PLWHA in the community to disclose their status. Effective strategies also need to be evolved that will target those not likely to disclose their status to anybody.